Post-transcriptional Gene Regulation in Colitis Associated Cancer - Chen, Gang; Feng, Yuan; Li, Xuezheng; Jiang, Zhe; Bei, Bei; Zhang, Lin; Han, Yueqing; Li, Yanwu; Li, Ning (Frontiers in Genetics, 2019)
Colitis-associated cancer (CAC) has been linked to microRNA (miRNA) aberrant expression elicited by inflammation. In this study, we used the AOM/DSS-induced CAC mice model to explore the ectopic expression of miRNAs in the precancerous stage of CAC. As a result, we found that miR-31-5p, miR-223-3p, and let-7f-5p were dysregulated during the development of intestinal dysplasia. Subsequently, we first identified the role of these three miRNAs in CAC. Adenomatous polyposis coli (APC) was revealed as a new target of miR-223-3p, and solute carrier family 9- subfamily A-member 9 (SLC9A9) and APC membrane recruitment protein 3 (AMER3) were suggested as two new targets for let-7f-5p. For miR-31-5p, we proved that it can target LATS2 mRNA so as to modulate Hippo pathway in Caco2 cells. Second, to examine if targeting these three miRNAs would lead to CAC prevention, pedunculoside, a natural triterpene glycoside capable of rescuing the down-regulation of LATS2 and APC caused by either miR-31-5p or miR-223-3p overexpression, respectively, was used in the in vivo AOM/DSS-induced CAC model. The results showed that pedunculoside (25 mg/kg) substantially mitigated the damage to mice intestine caused by DSS/AOM. These results suggested that miRNAs-elicited post-transcriptional regulation is involved in the pathogenesis of CAC, and CAC can be prevented through targeting key miRNAs that are ectopically expressed in CAC.